RAHASIA ISIM MUFRAD, MUTSANA DAN JAMAK DALAM BAHASA ARAB - Jimatul Arrobi; Oman Karya Suhada (SHAWTUL ARAB, 2022)
Among the characteristics of the Arabic language is the change in the form of mufrad, mustanna and plural. This study aims to reveal the morphosemantic secrets of the isim mufrad, mustanna and plural. This research was conducted using a descriptive method with a content analysis model. The source of the data is a number of vocabularies of the isim mufrad, mustanna and plural which are obtained from various sources and literature. The conclusion of this research is that there are secrets and uniqueness in the morphosemantics of the isim mufrad, mustanna and plural. Among them 1). plural words that have no mufrad form, 2). words that have a plural meaning and have no mufrad form, 3). a word that has a plural meaning and there is no mufrad form of the lafadz but there is a mufrad form of its meaning, 4). words that have mufrad and plural meanings. 5). a word that means plural with ta 'marbutoh. 6). the word mufrad which means plural and the form of the mufrad with ta' marbutoh, 7). Words that have a plural meaning and their mufrad form with ya nisbat, 8). the word mufrad which has mutsana but does not have the plural form of its lafadz, 9). the word mufrad which has a plural but does not have mutsanna, 10). said mustanna who has no mufrad